Investigation of Open Source Optimizers for Mechanical Design Optimization Problems - ., Muhammad Izwan Bin Hazim (IRC, 2016)
Open source optimizers are capable to solve mechanical engineering design optimization problem which are solving the objective function of each optimization problem. A few optimization problem was selected which are spring design, welded beam design and pressure vessel design and this problem are benchmark problem which is commonly used design problem from previous researchers. The aim of this study to investigate the optimization problems and available open source optimizers, to determine the benchmark problems and suitable optimizers to solve the benchmark problem and also to develop and writing source code for optimizers for each benchmark problems. There are many type of optimization software that can be used, but in this research focusing on open source optimizers which is pyOpt.